Effects of international debt on the economic development of small countries. - KAMINARIDES, John (1993)
Presents a comparative analysis of the effects of international debt on small countries, grouped by income. Concludes that international debt affects small countries with relatively higher incomes in a significantly different manner than it affects small countries with low incomes.